Estudo comparativo de métodos de estimativa de evapotranspiração potencial no Projeto Esecaflor-LBA, Caxiuanã – PA - TAVARES, Alexandra Lima (2019)
The present work was made in the National Forest of Caxiuanã, located in the city of Melgaço - Pará, about 400 km distant of Belém (01°42'30” S; 51°31'45” W; 16m of altitude). The used data mention the period from January of 2003 till August of 2008, of the project “Impact of Prolonged Drought in the Water and Carbon Dioxide Flows in an Amazonian Tropical Forest” (ESECAFLOR - LBA). The objective was to study the potential evapotranspiration in the National Forest of Caxiuanã, through some methods of estimates, in order to give subsidies to other studies of interactions between forest and the atmosphere. The results had indicated that the Penman-Monteith, Priestley-Taylor and Thornthwaite methods, had been most consistent, with minimum values during the rainy period and maximum values during the less rainy period of the region, suggesting it for application for the estimate of potential evapotranspiration.